Design of magnetic field configuration for controlled discharge properties in highly ionized plasma. (20th July 2015) - Alami, Jones; Stranak, Vitezslav; Herrendorf, Ann-Pierra; Hubicka, Zdenek; Hippler, Rainer
Abstract: In the present article, the effect of magnetic field design on electron and ion properties in both a metallic Ti/Ar and a reactive Ti/Ar + O2 high power impulse magnetron sputtering (HiPIMS) discharges is investigated. For the purpose, a variable magnetron with defined imbalance and geometrical coefficients K and, respectively, was utilized. The electron density, the mean electron energy, the plasma potential, and the floating potential were determined by employing time-resolved Langmuir probe measurements, for four specified magnetic field configurations. Mass spectroscopy was used in order to determine the energy distribution function of metal (Ti + , Ti 2+ ) and gaseous (Ar + , Ar 2+ , O + , O ) ions. Analysis of the measured data shows that the magnetic field design dramatically affects the charged particles energy- and spatial-distribution, causing a change in the plasma properties. It is concluded that a well-determined configuration of the magnetic field is necessary in order to insure discharge stability and reproducibility.